Kajian Yuridis Tentang Sanksi Kebiri Dalam Sistem Pemidanaan Di Indonesia Berdasarkan Undang Undang Nomor 17 Tahun 2016 Tentang Perlindungan Anak - Warsiman Warsiman (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
Indonesia is one of signatory member of the United Nations Convention on the Rights of the Children, which requires the State to guarantee that no children may suffer torture or other cruelty, whether it is humane action or degrading treatment or punishment. Protection of children in criminal cases is categorized as special protection that requires special treatment in handling the cases.Decency crimes generally lead to condemnation from the community; it especially comes from parents that happen to girls and boys, regarding the crime of rape, obscene acts, pedophiles and others. The arrangements that can be imposed on perpetrators prior to the existence of special laws governing pedophiles namely articles 289, 290, 292, which are regulated in the Criminal Code and articles 81, 82 and article 76D which are regulated in Law No. 16 of 2017 on the amendment of Law No. 23 of 2002 concerning children protection.In law No. 17 of 2016 amendment to Law No. 23 of 2002 concerning child protection, it is stated in law No. 16 of 2017 enhances the sanctions for the child sexual violence perpetrators, namely by chemical castration or injection of chemical liquids and installing chips as electronic detection devices. Such actions will be punished within a maximum period of two years and it is implemented after the convict is serving a basic sentence. Perpetrators may also be subject to additional penalties in the form of announcements of the perpetrator's identity because the actions and additional penalties are excluded for the child perpetrators . Keywords : Child, Decency Crime, Pedophile, Chemical Castration Punishment,